Bright lights, big Christmas : a novel [large type] - Andrews, Mary Kay, 1954- (Thorndike Press large print dynamic drama., 2023)
"It's a long way from a Christmas tree farm in North Carolina to a certain street corner in Greenwich Village, but Kerry Tolliver agrees to make the trek and live in a tiny camper with her older brother out of family loyalty. Selling Christmas trees at the family's stand on the sidewalks of New York, Kerry is startled to find herself beginning to feel at home in this quirky little corner of the city and succumbing to the charms of Patrick and his adorable son Austin. When an elderly neighbor goes missing with the holidays approaching, Kerry discovers her new friends have become family... and maybe more"--